U-Shaped Association of the Heart Rate Variability Triangular Index and Mortality in Hemodialysis Patients With Atrial Fibrillation - Braunisch, Matthias C.; Mayer, Christopher C.; Werfel, Stanislas; Bauer, Axel; Haller, Bernhard; Lorenz, Georg; Günthner, Roman; Matschkal, Julia; Bachmann, Quirin; Thunich, Stephan; Schlegl, Michaela; Ludwig, Maximilian; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Atrial fibrillation (AF) is common in hemodialysis patients and contributes to increased mortality. We aimed to examine heart rate variability triangular index (HRVI) in hemodialysis patients with AF as it has recently been reported to predict mortality in AF patients without kidney disease. Methods: A total of 88 patients on hemodialysis with a medical history of AF or newly diagnosed AF underwent 24-h electrocardiography recordings. The primary endpoint of cardiovascular mortality was recorded during a median follow up of 3.0 years. Risk prediction was assessed by Cox regression, both unadjusted and adjusted for the Charlson Comorbidity Index and the Cardiovascular Mortality Risk Score. Results: Median age was 76 years, median dialysis vintage was 27 months. Altogether, 22 and 44 patients died due to cardiovascular and non-cardiovascular causes. In 55% of patients AF was present during the recording. Kaplan-Meier plots of HRVI quartiles suggested a non-linear association between HRVI, cardiovascular, and all-cause mortality which was confirmed in non-linear Cox regression analysis. Adjusted linear Cox regression revealed a hazard ratio of 6.2 (95% CI: 2.1–17.7, p = 0.001) and 2.2 (95% CI: 1.3–3.8, p = 0.002) for the outer quartiles (combined first and fourth quartile) for cardiovascular and all-cause mortality, respectively. Patients in the first quartile were more likely to have sinus rhythm whereas patients in the fourth quartile were more likely to have AF. Conclusions: We found a U-shaped association between HRVI and mortality in hemodialysis AF patients. The results might contribute to risk stratification independent of known risk scores in hemodialysis AF patients.